Thermo-economic performance limit analysis of combined heat and power systems for optimal working fluid selections. (1st June 2023) - Yang, Xiaoxian; Yang, Fubin; Yang, Fufang
Abstract: In previous works, we have proposed the thermodynamic performance limit analysis methodology for the organic Rankine cycle for analyzing the impact of working fluid properties on system performance. Here the concept is extended to the thermo-economic performance limits, and is applied to a combined heat and power system based on an organic Rankine cycle. Working fluids are characterized with 8 characteristic thermodynamic and transport properties based on a corresponding state model and a residual entropy scaling approach. The 8 fluid characteristic properties along with 3 system operational parameters are optimized using a multi-objective genetic algorithm; a Monte Carlo algorithm is further adopted to avoid sub-optimal convergences. As the result, the performance limits could be well represented by the trade-off (Pareto front) between the maximized thermal efficiency and minimized payback period. The impact of the fluid characteristic properties on both thermodynamic and economic targets is investigated and ultimately guided the choice of working fluids: low molar mass, low thermal conductivity scaling factor, high viscosity scaling factor and high critical pressure are always preferred. "Wet" working fluid is preferred for a high thermal efficiency while "dry" working fluid is favored for a short payback period. Critical temperature has the most profound impact, while ideal gas isobaric heat capacity and acentric factor have negligible impacts. The choice of working fluid, system design (e.g., recuperative effectiveness) and system operational parameters (e.g., evaporation temperature) highly depends on the given hot sources and the preferences to the thermodynamic and economic targets. Graphical abstract: Image 1 Highlights: Proposed an analysis framework for the thermo-economic performance limits of CHP. Determined thermo-economic performance limits and optimal working fluid features. Investigated impacts of fluid properties on the thermo-economic targets. Provided guidelines for working fluid selection.